Formation of Stable Complexes Between Urokinase and a Human Urinary Component - Cieplak, Witold; Hart, David A (Thrombosis and Haemostasis, 1985)
Human urine was found to contain multiple species of urokinase (UK)-like plasminogen activator (PA) activity when subjected to concentration and/or dialysis and analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and zymography. Untreated, freshly voided urine contained only Mr = 52,000 and 35,000 UK while dialyzed or undialyzed urine concentrates contained additional PA activity at Mr = 80,000 and 95.000. SDS-PAGE of incubation mixtures of radioiodinated UK (Mr = 52,000 or 35,000) and urine concentrates revealed the presence of radiolabeled complexes with MrS of 80,000 and 95.000. The bond(s) involved in complex formation was also relatively resistant to heat and reduction. Treatment of radioiodinated UK with the serine proteinase inhibitor, p-nitrophenyl guanidinobenzoate, prior to incubation with dialyzed, concentrated urine prevented formation of the complexes. In addition, the enzymatic activity of the Mr = 80,000 and 95,000 species was unaffected by diisopropyl fluorophosphate. These results indicate that UK forms SDS-stable complexes with a urinary component that has a Mr of approximately 40,000. The results further suggest that these complexes express PA activity when analyzed by SDS- PAGE and zymography.
Keywords: Urokinase; Zymography; Complexes; Urinary binding component